STRAW STIFFNESS IN LANDRACES OF TWO-ROW BARLEY (HORDEUM VULGARE L.) - Jaff, D. M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to investigate straw stiffness in land races of two- row barley (hordeum vulgarel.). Straw from four landrace populations of barley grown in the Kurdistan Region of Iraq was measured and tested for bending stiffness, showing considerable variation in diameter and in longitudinal bending modulus. In the lower range of diameter, the straw from these landrace populations was highly flexible and was able to lodge without fracture, by curving elastically without fracture or buckling until the head reached the ground. The landrace populations studied contained substantial variation in internode diameter and in the stiffness of the wall material. Selection for internode diameter appeared to have potential for improving lodging resistance. Because lodging potential depends on the weight of the whole shoot as well as on wind forces, it is likely to be increased by pre-harvest moisture content. Decreasing moisture content of the straw and heads reduced the total above-ground weight of the plant by approximately a factor of two during the month prior to harvest.